Mengungkapkan hikmah di balik pemujaan terhadap pengorbanan - Nurul ulfa; Luthfi karim (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Sacrifice is one of the most important acts of worship in Islam. It is mandatory for Muslims who are able to follow and obey the commands of Allah SWT. Apart from being a form of obedience to Allah SWT, sacrifice also contains social values ​​and concern for others. Through sacrifice, Muslims learn to share their good fortune with others, especially those who are less fortunate. Therefore, this research aims to describe how the wisdom behind sacrificial worship can bring a deeper understanding of the importance of sacrificial worship in the lives of Muslims, as well as how sacrifice can provide broad benefits for individuals and society at large. This research uses research methods that are used as a type of library research or literature study which includes collecting, reading, recording and processing data from various library sources such as books, magazines and other sources. The research results show that sacrificial worship has a number of teachings that cover many spiritual, social, economic and educational aspects. These studies provide a clearer picture of the breadth and depth of the wisdom behind sacrifice, as well as how this practice remains relevant and beneficial in various aspects of Muslim life.